2014
DOI: 10.1128/aac.02637-13
|View full text |Cite
|
Sign up to set email alerts
|

How To Minimize Toxic Exposure to Pyridine during Continuous Infusion of Ceftazidime in Patients with Cystic Fibrosis?

Abstract: Ceftazidime is particularly efficient against Pseudomonas aeruginosa in cystic fibrosis patients. Thus, the spontaneous production of pyridine, which is a toxic product, raises some concern. Our aim was to examine the kinetics of degradation of ceftazidime in portable infusion pumps either at 4°C, 22°C, or 33°C and to propose some recommendations in order to reduce the pyridine exposure. Two administration models were studied in vitro. In model 1, we administered 12 g of ceftazidime infused over 23 h (once-dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…It was found that 10% of the ceftazidime was degraded after an average of 19 h 11 min (n = 4) and 0.79% (n = 4) of pyridine was formed after 24 h. Figures 3 and 4 show the results obtained with one of the PEIPs as an example of this degradation. The increase in concentration of pyridine present in the solution is in line with findings from literature [9,10]. Typical chromatograms obtained at 254 and 285 nm with a sample taken from a PEIP at 20 h are shown in Fig.…”
Section: First Set Of Experiments With a Starting Dose Of 6 G Of Ceft...supporting
confidence: 90%
See 3 more Smart Citations
“…It was found that 10% of the ceftazidime was degraded after an average of 19 h 11 min (n = 4) and 0.79% (n = 4) of pyridine was formed after 24 h. Figures 3 and 4 show the results obtained with one of the PEIPs as an example of this degradation. The increase in concentration of pyridine present in the solution is in line with findings from literature [9,10]. Typical chromatograms obtained at 254 and 285 nm with a sample taken from a PEIP at 20 h are shown in Fig.…”
Section: First Set Of Experiments With a Starting Dose Of 6 G Of Ceft...supporting
confidence: 90%
“…Curti et al examined the stability of a 40 mg/mL ceftazidime solution in saline over 8 h at ambient temperature when stored in 50 mL polypropylene syringes and found that the solution was stable [9]. Ceftazidime aqueous solutions at concentrations around 53 mg/mL in PEIPs were checked by Bourget et al at a temperature of 33°C over 23 h [10]. In these conditions, ceftazidime was stable for only 12 h.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of the 2 mg PDE26 27 standard for pyridine exposure means the old standard of the 1.1 mg/mL25 should be disregarded. Bourget et al ,29 measured the total delivered amount of pyridine over various full-day infusions comparing two 6 g infusion over 11.5 hours each for a total of 23 hours of run-out and a single 23 hours infusion of 12 g. This split method (2×6 g infusions) was tested to try to reduce the total daily exposure of pyridine. Although it was a successful reduction, the amount of pyridine the patient still received was 26.4 mg and 30.4 mg when run-out at 22°C and at 33°C, respectively.…”
Section: Discussionmentioning
confidence: 99%